2020
DOI: 10.1177/0363546520949204
|View full text |Cite
|
Sign up to set email alerts
|

Performance and Return to Sport After Excision of the Fractured Hook of the Hamate in Professional Baseball Players

Abstract: Background: A fracture of the hook of the hamate is a common injury affecting professional baseball players. The treatment for these fractures ranges from nonoperative immobilization to excision of the fragment. Purpose/Hypothesis: The purpose was to report the results of surgical treatment of hook of hamate fractures in professional baseball players and determine which factors are associated with return to sport (RTS) and time to RTS. The hypothesis was that there is a high rate of RTS in professional basebal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…A recent database review of 261 Major League Baseball players showed that 81% of players return to the same or higher level of play at a mean of 48 days. 9 Usage increased postoperatively, but batting statistics slightly declined. A similar study found that the wins-above-replacement statistic was unchanged in athletes from pre- to postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…A recent database review of 261 Major League Baseball players showed that 81% of players return to the same or higher level of play at a mean of 48 days. 9 Usage increased postoperatively, but batting statistics slightly declined. A similar study found that the wins-above-replacement statistic was unchanged in athletes from pre- to postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with symptomatic pseudoarthrosis of the hamate hook, some authors prefer to perform resection of the hook. 51 However, the hamate hook works as a pulley for the flexor tendons of the ring and small fingers in ulnar deviation or during firm gripping of the wrist. Moreover, important ligaments such as the hamatometacarpal and hamatotriquetral ligaments originate in the hook.…”
Section: Fractures Backgroundmentioning
confidence: 99%
“…In a study of all Major League Baseball athletes sustaining fractures of the hook of the hamate between 2010 and 2017, 81% of athletes were able to return at the same level of play. 9 Clearly, educational programs emphasizing specific mechanisms of injury, earlier diagnosis, more expedient treatment, and optimum rehabilitation may decrease the overall morbidity of this injury. Most important, and often not discussed, are improved approaches to prevent this injury before it occurs, to minimize its morbidity.…”
mentioning
confidence: 99%